Affinity studies of hypocrellin B and mono-cysteine substituted hypocrellin B with CT-DNA using spectroscopic methods. Issue 5 (2005) - Wei Wei, Shaohua Shaohua; Zhou Zhou, Jiahong Jiahong; Feng Feng, Yuying Yuying; Huang Huang, Deyin Deyin; Wang Wang, Xuesong Xuesong; Zhang Zhang, Baowen Baowen; Shen Shen, Jian Jian
Abstract : The interaction of anticancer drug hypocrellin B (HB) and mono-cysteine substituted hypocrellin B (MCHB) with calf thymus deoxyribonucleic acid (CT-DNA) has been investigated using spectral methods. The results of UV–visible spectra showed that the HB and MCHB can intercalate into the base-stacking domain of the CT-DNA double helix. Further studies based on fluorescence spectroscopy and circular dichroism (CD) spectroscopy also supported the intercalation mechanism.